Analisis Kegagalan Sistem Kontrol Pitch Propeller pada Kapal MT. Transko Aquila Menggunakan Metode Failure Mode and Effects Analysis (FMEA) - Hidayatullah, Anton; Suwasono, Bagiyo; Awwalin, Rodlitul (Jurnal Inovasi Global, 2025)
The Controllable Pitch Propeller (CPP) system is a crucial ship propulsion technology in supporting precision maneuvers, especially in narrow harbors without the assistance of tugboats. This study examines the failure of the CPP system on MT ships. Transko Aquila during the movement at Pertamina Reo's TBBM port, NTT, focusing on identifying technical, operational, and managerial factors that affect system reliability. The purpose of the study was to evaluate the impact of failures on operational efficiency and shipping safety, as well as to formulate data-driven recommendations for system improvement. The methods used are a qualitative descriptive approach with direct observation techniques, crew interviews, documentation studies, and Failure Mode and Effects Analysis (FMEA) analysis. Analysis was carried out on ten critical components of the CPP system, with assessments based on severity, frequency of occurrence, and detection ability. The results showed that the failure mode with the highest RPN value occurred in the pitch control mechanism (RPN = 216), hydraulic pump (RPN = 200), and oil cooling system (RPN = 128). Faults identified include undesirable pitch reversal, decreased hydraulic pressure, delayed control system response, and decreased RPM of the main engine. The impact includes a ±3-hour delay in docking, increased risk of collisions, and activation of emergency safety protocols. The FMEA approach has proven effective in providing comprehensive risk maps, supporting technical decision-making, and improving the reliability of the ship's propulsion system overall.